Celiac disease, collagenous sprue and microscopic colitis in IBD. Observations from a population-based cohort of IBD (ICURE). (October 2015) - Rönnblom, Anders; Holmström, Tommy; Tanghöj, Hans; Wanders, Alkwin; Sjöberg, Daniel
Abstract Objective. Inflammatory bowel disease (IBD), microscopic colitis and celiac disease are all diseases with worldwide distribution and increased incidence has been reported from many areas. There is a shortage of studies investigating the occurrence of these diseases in the same individual and whether those affected demonstrate any particular phenotype. The aim of the study was to describe the concomitant incidence of microscopic colitis and celiac disease in a population-based IBD cohort. Methods. All 790 individuals in a prospective population-based cohort included 2005–09 from Uppsala region, Sweden, were reviewed regarding the appearance of microscopic or celiac disease before or after IBD diagnosis. Results. Fifty percent (396/790) of the patients had been examined for the possibility of celiac disease. Seventeen patients with celiac disease were found, representing 2.2% of the cohort. Patients with celiac disease were younger compared to the non-celiac patients and those with colitis had more often an extensive inflammation of the colon. Seventy-one percent (12/17) were women. The majority of the patients were diagnosed with celiac disease before IBD. Five patients with IBD had an earlier diagnosis of microscopic colitis or developed it after the IBD diagnosis. One teenager developed collagenous sprue, misinterpreted as a severe relapse of ulcerative colitis (UC) resulting in colectomy. Conclusions. The risk for celiac disease seems not to be increased in IBD, but those affected by both diseases seem to be predominantly women with extensive UC. There is a potential association between microscopic colitis and IBD.